Transarterial chemoembolization for unresectable hepatocellular carcinoma: a comparative study between transradial and transfemoral approaches - Bo, Shun-Ting; Zhu, Jun; He, Li-Xiao; Zhu, Xiao-Li (Frontiers in Oncology, 2025)
BackgroundWhile transarterial chemoembolization (TACE) has been performed using both the transfemoral approach (TFA) and the transradial approach (TRA) to date, the relative superiority of these techniques remains uncertain. This study aimed to evaluate the relative clinical efficacy, radiation exposure, and safety associated with TRA- and TFA-based TACE procedures in patients with inoperable hepatocellular carcinoma (HCC).MethodsThis study compared the relative outcomes of consecutive inoperable HCC patients who were treated via TFA- or TRA-based TACE between January 2020 and August 2024.ResultsThis retrospective analysis included 83 HCC patients, of whom 41 and 42 respectively underwent TFA- and TRA-based TACE. Both of these approaches were associated with technical success rates of 100%. The mean TACE duration in the TRA group was significantly shorter than that in the TFA group (57.4 ± 23.5 vs. 73.5 ± 23.3 min, P = 0.002), whereas both groups exhibited a similar median fluoroscopy time (14 min vs. 13 min, P = 0.415) and radiation dose (159 Gy.cm2 vs. 160 Gy.cm2, P = 0.946). Two patients in each group experienced puncture site hematomas (4.9% vs. 4.8%, P = 1.000). While patients in the TFA group required ≥ 20 h of postoperative bed rest, the same was not true for patients in the TRA group.ConclusionTRA- and TFA-based TACE are both safe and feasible approaches to treating inoperable HCC patients. Relative to the TFA-based approach, the TRA-based approach entails a significantly shorter arterial compression time and requires less postoperative bed rest.